Seismic Assessment of Sssi Effects Between Adjacent Cross-Laminated Timber (Clt) Buildings - Saavedra-Flores, E; Torres-Olivares, S (Elsevier Ltd, 2024)
Urban building designs have been performed considering the behaviour of individual structures in isolation, neglecting potential seismic interactions with neighbouring buildings. In densely populated metropolitan areas, the Structure–Soil–Structure Interaction (SSSI) becomes a significant factor, capable of either amplifying or reducing the seismic response of buildings. This suggests that there is an unquantified seismic risk in densely packed urban areas, which will need to be estimated to obtain designs for more resilient infrastructure. Despite the increasing popularity of CLT as a structurally competitive material, limited attention has been given to investigating dynamic interactions between timber structures. The reduced weight of CLT structures compared to traditional materials necessitates a focused examination of the effects imposed by nearby buildings under varying soil conditions, challenging the fixed-base assumptions commonly applied in seismic analyses. This study investigates the impact of SSSI between pairs of cross-laminated timber (CLT) buildings. Three distinct building heights are considered, exploring differences in storey ratios, under five different ground motions to evaluate seismic performance comprehensively. Sixty detailed high-order three-dimensional models, treating soil and buildings as unified systems, are developed as numerical dynamic simulations. Results reveal that SSSI can significantly influence the displacement and acceleration demands of buildings, with a more pronounced effect observed in loose soil conditions. Particularly, the presence of adjacent higher buildings leads to an increase in the seismic response of the smaller structure, showing amplification effects in peak values but maintaining similar dynamic behaviour. There has been observed a clear trend of increase in the roof displacements of the smaller structure when the storey ratio of neighbouring structures increases; however, the trend of behaviour is not clear in the maximum accelerations. The study underscores the importance of understanding how nearby buildings, particularly those with more storeys, can impact the seismic response on CLT structures. © 2024 Institution of Structural Engineers